Evaluating a palliative care services: our experience of the role of "a professional users" survey" as an evaluating tool. (29th September 2015) - Anderson, A-K; Breen, M
Abstract : Evaluating our paediatric palliative oncology outreach service to improve clinical effectiveness and facilitate changes, in line with standards set, is challenging. The authors utilised the tool of a "professional users' survey". Aims: To compare our paediatric oncology palliative care practice against the standards set by the "Improving outcomes in children with cancer, NICE, 2005" (IOG). Methods: The authors devised a professional users' survey. It consisted of thirty-eight questions directly taken from the standards stated in the paediatric palliative care section of the IOG. The questionnaire was divided into sections containing "yes/no" answers with comment boxes at the end of each section. The sections were: information and communication, end of life care, outreach visits, general practitioner (GP) meetings, symptom support and advice, out of hour's advice, symptom boxes, voluntary sector, allied health professionals, education and training and demographics regarding the respondent (including professional role and time in post). The postal questionnaire and cover letter were sent out to 24 community and paediatric oncology shared care hospitals (POSCU) teams (including shared care consultant, ward link nurses or clinical nurse specialist) and four children's hospices. The anonymous questionnaires were returned to our centre's audit department (an independent source) for collation of the results. Results: Our percentage response rate was: 50% hospice, 48% community nursing team and 43% POCSU (35% consultants, 20% nurses). The overall POSCU response calculation was based on whether at least one member of the team replied from a specific centre. Overall, the response was very positive. There were areas identified as needing improvement including communication to POSCUs, in particular providing regular written updates, and regular local training days including education around reasons for GP involvement. Conclusion: There are challenges in evaluating a service through a professional users' survey, including respondent apathy. Though when engaged, the professional users of a service provide valuable feedback into how to improve and enhance services effectively. This also enables them to feel they have buy-in into the changes that can be made as a result of the survey. From our view, it enables us to objectively direct improvements in our service.